2017
DOI: 10.1007/s11356-017-9986-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of some feed additives in fish fed on diets contaminated with cadmium

Abstract: The decline of cadmium pollution in fish farms is needed by any adequate method. The present study was designed to explore the effect of dietary cadmium contamination and its amelioration by using dietary clay, probiotic (Bactocell®), vitamin C, and vitamin E supplementation in Nile tilapia fish diet on growth rate, feed efficiency, blood components, and cadmium residues. Fish were separated into 15 groups, each group of fish was stocked into three aquaria and each contains 20 fishes. The fish of the first fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…In the present study, the growth performance of pearl gentian grouper was severely decreased by dietary 300 mg/kg dietary Cd exposure. Similar growth inhabitations by certain level of dietary Cd in inorganic form were confirmed in many other fish species, such as cobia (Rachycentron canadum L.) at 10.90 mg/kg (Liu et al, 2015), Nile tilapia(Oreochromis niloticus) at 25 mg/kg (Ayyat et al, 2017), rockfish (Sebasres schlegeli) at 25 mg /kg (Kim et al, 2004;Kang et al, 2005), yellow catfish (Pelteobagrus fulvidraco) at 48.57 mg/kg (Tan et al, 2010), genetic improvement of farmed tilapia (GIFT) at 100 mg/kg (Lu, 2014), crucian carp (Carassius auratus) at 120 mg/kg (Kim, 2009), and Parrotfish (Oplegnathus fasciatus) at 162 mg/kg (Okorie et al, 2014), and goldfifish (subspecies: Prussian carp Carassius auratus gibelio B.) at 10000 mg/kg (wet weight) (Szczerbik et al, 2006).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present study, the growth performance of pearl gentian grouper was severely decreased by dietary 300 mg/kg dietary Cd exposure. Similar growth inhabitations by certain level of dietary Cd in inorganic form were confirmed in many other fish species, such as cobia (Rachycentron canadum L.) at 10.90 mg/kg (Liu et al, 2015), Nile tilapia(Oreochromis niloticus) at 25 mg/kg (Ayyat et al, 2017), rockfish (Sebasres schlegeli) at 25 mg /kg (Kim et al, 2004;Kang et al, 2005), yellow catfish (Pelteobagrus fulvidraco) at 48.57 mg/kg (Tan et al, 2010), genetic improvement of farmed tilapia (GIFT) at 100 mg/kg (Lu, 2014), crucian carp (Carassius auratus) at 120 mg/kg (Kim, 2009), and Parrotfish (Oplegnathus fasciatus) at 162 mg/kg (Okorie et al, 2014), and goldfifish (subspecies: Prussian carp Carassius auratus gibelio B.) at 10000 mg/kg (wet weight) (Szczerbik et al, 2006).…”
Section: Discussionsupporting
confidence: 68%
“…Similar results were also shown in the studies of other fish species exposed to dietary Cd stress. The parameters of body composition were not affected by dietary Cd in turbot at 50 mg/kg (Cui et al, 2016), Japanese seabass at 12.08 mg/kg (Mai et al, 2006), and Nile tilapia fed dietary Cd at 25 mg/kg (Ayyat et al, 2017). In comparison, higher levels of moisture and ash and lower levels of crude protein and lipid were found in yellow catfish exposed to 48.75 mg/kg dietary Cd (Tan et al, 2010) and cobia exposed to 10.90 mg/kg dietary Cd (Liu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The Cd content in fish organs lowers when compared with those fed on a diet without humic acid supplementation. The obtained results indicated that humic acid as a feed additive could modify the liver and kidney function in fish to reduce the Cd accumulation (Ayyat et al, 2017). This ability may be due to humic acid is known to have containing functional groups such as carboxylic, carbonyl and phenolic groups, which can form complex bonds of minerals, and heavy metals (Islam et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Swimming performance was found to affect the appetite in fish groups exposed to increasing concentrations of cadmium which may be due to the inhibition of dopamine and serotonin involved in locomotion, aggression and feeding behaviour, in the presence of heavy metals. Study on the role of some feed additives in fish fed on diets contaminated with cadmium also showed that daily feed intake decreased significantly (p<0.001) with increasing dietary cadmium level Ayyat et al (2017).…”
Section: Journal Of Environmental Biology March 2019mentioning
confidence: 97%